Analisis Penguasaan Literasi Digital Mahasiswa - Widowati Pusporini; Devi Septiani; Titi Lestari (Universitas Sarjanawiyata Tamansiswa, 2022)
The Research and Evaluation Program of Education, Science Education, and English Language Education is a study program with a different science focus which have similarities in the final learning objective of preparing graduates to compete in the 21st century. This research aims to provide an overview of the mastery of digital literacy of students in 3 study programs in Universitas Sarjanawiyata Tamansiswa.This study is a research survey conducted for 2 months; sampling selection is using purposive sampling techniques. Instruments in the form of e-questionnaires were used to assess the ability of the level of mastery of digital literacy of students. Data from the questionnaire were analyzed using the Miles & Huberman analysis model. Based on the results of the questionnaire analysis showed that digital literacy in all three Study Programs had reached an excellent category. The percentage of digital literacy of students of the English Education study program amounted to 79.04, IPA Education by 80.82, and The Graduate Program of Education Research and Evaluation of 84.14.